A collaborative cardiologist-pharmacist care model to improve hypertension management in patients with or at high risk for cardiovascular disease - Brian K. IRONS (Pharmacy Practice, 2012)
Physician led collaborative drug therapy management utilizing clinical pharmacists to aid inthe medication management of patients with hypertension has been shown to improve bloodpressure control. With recommendations for lower blood pressures in patients with coronary artery disease, a cardiologist-pharmacist collaborative care model may be a novel way to achieve these more rigorous goals of therapy. Objective: The purpose of this project was toevaluate this type of care model in a high cardiac risk patient population. Methods: A retrospective cohort study determined the ability of a cardiologist-pharmacist care model(n=59) to lower blood pressure and achieve blood pressure goals (< 130/80 mmHg) in patients with or at high risk for coronary artery disease compared to usual cardiologist care (n=58) in the same clinical setting. Results: The cardiologist-pharmacist care model showed a higher percentage of patients obtaining their goal blood pressure compared to cardiologistcare alone, 49.2% versus 31.0% respectively, p=0.0456. Greater reductions in systolic bloodpressure (-22 mmHg versus -12 mmHg, p=0.0077) and pulse pressure (-15 mmHg versus -7 mmHg, p=0.0153) were noted in the cardiologist-pharmacist care model. No differences in diastolic blood pressure were found. There was a shorter duration of clinic follow-up (7.0 versus 13.2 months, p=0.0013) but a higher frequency of clinic visits (10.7 versus 3.45, p<0.0001) in the cardiologistpharmacist care model compared to usual care. The number of antihypertensive agents used did not change over the time period evaluated.